Post-Harvest N2O Emissions Can Be Mitigated With Organic Amendments - Rothardt, S.; Fuß, R.; Pahlmann, I.; Kage, H. (Frontiers in Environmental Science, 2021)
After harvest of winter oilseed rape and faba bean crops considerable high soil nitrate values may built up before winter in central to north European regions. In combination with high precipitation and a low N uptake by the subsequent crop in fall this causes a high risk for N2O emissions and nitrate leaching. Microbial decomposition of crop residues or high carbon amendments may immobilize mineral N temporarily and therefore may prevent losses by direct N2O emissions. Five treatments including crop residue removal and application of different organic amendments after harvest were tested in a field trial in Northern Germany to elucidate the potential of this mechanism as a mitigation option. N2O emissions and soil mineral nitrogen status were monitored from August to March in three consecutive years. Observed emissions range from 0.1 to 3.4 kg N ha-1 in 180 days. An empirical model approach was applied to separate the impact of spatially and temporally heterogeneous environmental conditions between the plots of the field experiment from treatment effects in the subsequent statistical analysis of N2O emissions. Results show that the exchange of the initial crop residues with organic amendments with high C:N ratios (i.e. winter wheat straw and sawdust) after harvest of faba bean or oilseed rape can reduce N2O emission during fall and winter by up to 45%.